1980
DOI: 10.1136/oem.37.4.399
|View full text |Cite
|
Sign up to set email alerts
|

Role of family susceptibility, occupational and family histories and individuals' blood groups in the development of silicosis.

Abstract: A previous investigation has shown that family susceptibility and occupational and family histories have a decisive role in the development of byssinosis among workers exposed to flax dust. Results of investigation of silicosis in 814 male workers exposed to silica-bearing dust showed that family susceptibility has an important role in the development of silicosis among examined workers, and workers whose fathers had an occupational history of exposure to silica-bearing dust were more resistant to the developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1986
1986
1989
1989

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…to fibrogenesis are still poorly understood. The biological characteristics of the dusts are largely unknown, although it is suggested that the dust size, shape, surface charge, roughness, surface chemical composition, trace metal content, and crystallinity; dose of silica in the ambient air of the workplace; duration of exposure; genetic variation in exposed subjects; personal respiratory patterns; and presence of any coexisting disease (such as tuberculosis or rheumatoid arthritis) all influence the expression of silicosis (Koskinen et al, 1983;Noweir et al, 1980;Raask and Schilling, 1980;Reiser and Last, 1979;Thorne et al, 1985;Wolff et al, 1981). The actual biochemical mechanisms through which these factors operate are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…to fibrogenesis are still poorly understood. The biological characteristics of the dusts are largely unknown, although it is suggested that the dust size, shape, surface charge, roughness, surface chemical composition, trace metal content, and crystallinity; dose of silica in the ambient air of the workplace; duration of exposure; genetic variation in exposed subjects; personal respiratory patterns; and presence of any coexisting disease (such as tuberculosis or rheumatoid arthritis) all influence the expression of silicosis (Koskinen et al, 1983;Noweir et al, 1980;Raask and Schilling, 1980;Reiser and Last, 1979;Thorne et al, 1985;Wolff et al, 1981). The actual biochemical mechanisms through which these factors operate are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…While chronic bronchitis is often regarded as the most important clinical feature of any pneumoconiosis, the question ofwhether it precedes and promotes the development ofradiologically recognizable pneumoconiosis is affirmed by some authors (38) and negated by others (95).…”
Section: Accompanying Diseasesmentioning
confidence: 99%